Retrospective Analysis of Early Impact of COVID-19 on Systemic Cancer Treatment—A Pilot Study - Pattiyeil, Anakha; Antony, Febin; Cyriac, Sunu L; Jose, Anilkumar; P., Jini M. (Indian Journal of Medical and Paediatric Oncology, 2021)
Introduction Cancer care during the coronavirus disease 2019 (COVID-19) pandemic is challenging as the patients are at an increased risk of developing complications compared with the general population.Objectives This study was conducted to assess the impact of COVID-19 pandemic and nationwide lockdown on systemic cancer care.Materials and Methods This comparative descriptive study was conducted in the Department of Medical Oncology and Haematology in a tertiary care center in India. The study compared and analyzed the consecutive patient data of two different units in the Department of Medical Oncology in the pre-COVID phase (PCP) and post lockdown relaxation phase (PLRP). We represented the categorical data in frequency and percentage, and chi-squared test was used to analyze the variables.Results Patients were categorized based on demographic, disease-related, and hospital visit-related parameters and a significant drop noted in patients who utilized a prebooking facility (p = 0.0001), in the number of patients aged >50 years (p = 0.004), number of patients who presented with hematological malignancies (p = 0.006), and who came for follow-up (p = 0.0001). The other parameters remained statistically insignificant.Conclusions During PLRP, active systemic cancer care seems to have been less affected, whereas follow-up of patients and visits of elderly patients were significantly reduced. If the pandemic remains under control, cancer care may not get compromised. This shows the importance of flattening the curve for quality management of other diseases during a pandemic.
Keywords: COVID-19; cancer care; lockdown; pre-COVID phase; pandemic; early impact